Effect of pectinase enzyme treatment conditions on quality of morus alba l. Fruit extract - Nguyễn Hoàng Thảo Ly; Lê Sĩ Ngọc; Nguyễn Minh Xuân Hồng (Journal of Technical Education Science, 2018)
This paper investigated the effect of pectinase enzyme treatment conditions on quality of Morus alba L. fruit extract. The white mulberrypurée was treated with enzyme Pectinex (Novozyme) at different concentration (0; 0.2; 0.4; 0.6; 0.8%) and incubated at 45oC in different time periods (1, 2, 3 hours). The extraction efficiency and the quality of white mulberry fruit juice extract were evaluated and compared with the untreated one. The results showed that treatment with Pectinex enzyme at 0.6% concentration for 2 hours gave higher extraction efficiency (86.26%) than untreated one (57.11%). The quality of extracted juice was also better with higher total sugar content (9.59%), reducing sugar content (1.77%) and total polyphenol content (65.59 mg GAE/g).